PENGARUH KUALITAS PELAYANAN, CITRA RUMAH SAKIT DAN KEPERCAYAAN TERHADAP KEPUASAN PASIEN DAN IMPLIKASINYA PADA LOYALITAS PASIEN - Afrizal Afrizal; Suhardi Suhardi (JEM Jurnal Ekonomi dan Manajemen, 2018)
This study aims to examine service quality, hospital image and trust in patient satisfaction and its implications for patient loyalty. By using a sample of 136 patients in the dental polyclinic of PT Bakti Timah Hospital in Pangkalpinang, this study used a structural equation model to test the causality between latent variables in accordance with those hypothesized. The results showed that the variables of service quality, hospital image, the trust had a significant effect on patient satisfaction. The variables of hospital and trust image have the greatest influence on satisfaction. The results of the study are expected to add variables beyond service quality, hospital image, and organizational trust. Subsequent research can broaden the scope of the study to either the variable or the scope of the study so that a full portrait of the patient's perception in Pangkalpinang Bakti Timah Hospital will be seen as a whole.